SPECIFIC FEATURES OF MORPHOLOGICAL CHANGES IN THE MAMMARY GLAND UNDER THE INFLUENCE OF VARIOUS RISK FACTORS IN EXPERIMENTAL ATHEROSCLEROSIS - Islomov Sardor Doniyor o’g’li (TADQIQOTLAR, 2025)
Abstract This article analyzes the mechanisms of development of atherosclerosis under experimental conditions, the dynamics of morphological changes in the mammary glands, and the role of various risk factors such as dyslipidemia, hormonal imbalance, hypodynamia, and stress. Experimental studies revealed that atherosclerotic processes significantly affect the microcirculatory system, alveolar structure, and secretory function of the mammary gland. The findings deepen the understanding of the pathogenesis of atherosclerosis and its influence on hormone-dependent organs, contributing to the development of preventive and therapeutic approaches.